The identity of Dicranomyia (Dicranomyia) luteipennis Goetghebuer (Diptera, Limoniidae) - Starý, Jaroslav (Zootaxa, 2009)
x Dicranomyia (Dicranomyia) luteipennis Goetghebuer in Goetghebuer & Tonnoir, 1920 is revised and its diagnostic characters are elucidated. Descriptions are provided of three closely related species, viz. D. (D.) fuscinota sp. n. (Bulgaria, Czech Republic, Italy, Slovakia, Switzerland), D. (D.) magninota sp. n. (Spain) and D. (D.) pallidinota sp. n. (Bulgaria, Greece, France (Corsica), Lebanon, Syria). D. (D.) lorettae Geiger, 1985 and D. (D.) mattheyi Geiger, 1985 are redescribed. All important characters of the male terminalia and the wing pattern are illustrated. Distribution of the species is checked and some new country records are presented.